PENAMPILAN DAN RASA MAKANAN SEBAGAI FAKTOR SISA MAKANAN PASIEN ANAK DI RUMAH SAKIT Dr. SOBIRIN MUSI RAWAS - Yuliantini, Emy (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
The purpose of this study was to determine the relationship of the patient'sappearance and taste of the food with the rest of the food in the child's room inpatient hospitalDr. Sobirin Musi Rawas in 2013. This research uses a cross-sectional design with purposivesampling technique. With the independent variable ( the appearance and taste of food thepatient ) and the dependent variable (food scraps ). The subjects were patients hospitalizedchildren total sample of 40 people that match specified criteria were respondents. Analysis ofthe chi-square test statistic with 95% confidence level and using SPSS. The results of theresearch relationship with the appearance of food waste was found that patients whoexpressed the food looks attractive with good leftovers as much as 60 %. There is nosignificant correlation between the appearance presented by the rest of the food ( ρ = 0.191 ).The results of the research relationship with the taste of food leftovers found that patients whoexpressed the taste of food in accordance with the rest of the good food that is as much as 62.1%. There was a significant association between the taste of food with leftovers patients ( ρ =0.034 and OR = 7.364 value ).